1999
DOI: 10.1038/sj.onc.1202452
|View full text |Cite
|
Sign up to set email alerts
|

Level of retinoblastoma protein expression correlates with p16 (MTS-1/INK4A/CDKN2) status in bladder cancer

Abstract: Recent studies have shown that patients whose bladder cancer exhibit overexpression of RB protein as measured by immunohistochemical analysis do equally poorly as those with loss of RB function. We hypothesized that loss of p16 protein function could be related to RB overexpression, since p16 can induce transcriptional downregulation of RB and its loss may lead to aberrant RB regulation. Conversely, loss of RB function has been associated with high p16 protein expression in several other tumor types. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
64
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 26 publications
13
64
1
Order By: Relevance
“…Although it is generally assumed that tumor suppressors are negative regulators of tumor formation and are often down-regulated in cancer development, observations of over-expression of TS proteins such as pRb, p53, p73, p27, p16 in di erent tumors are not uncommon Doki et al, 1997;Kaur et al, 1998;Shapiro et al, 1995;Warneford et al, 1991;Yokomizo et al, 1999). The over-expression of a tumor suppressor may imply a compensatory mechanism which may function to circumvent the disrupted regulatory pathway of wild-type TS protein (Benedict et al, 1999;Emig et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally assumed that tumor suppressors are negative regulators of tumor formation and are often down-regulated in cancer development, observations of over-expression of TS proteins such as pRb, p53, p73, p27, p16 in di erent tumors are not uncommon Doki et al, 1997;Kaur et al, 1998;Shapiro et al, 1995;Warneford et al, 1991;Yokomizo et al, 1999). The over-expression of a tumor suppressor may imply a compensatory mechanism which may function to circumvent the disrupted regulatory pathway of wild-type TS protein (Benedict et al, 1999;Emig et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Since not all super®cial papillary tumors in humans harbor Ha-ras mutations, our study can not exclude the possibility that other genetic defects can also cause the super®cial, papillary variant of bladder tumors. For instance, the defect of p16, a cyclin-kinase inhibitor and tumor suppressor, has recently been shown to be associated with human super®cial papillary tumors (Orlow et al, 1995;Balazs et al, 1997;Benedict et al, 1999). Studies are underway to determine the potential involvement of p16 defect in the activated ras-induced transgenic bladder tumors.…”
Section: Different Genetic Defects Underlie Two Phenotypic Variants Omentioning
confidence: 99%
“…Baud et al 41) suggested that simultaneous loss of both CDKN2 alleles, by point mutation or homozygous deletion, was infrequent in primary bladder cancers. In a more recent study, Benedict et al 42) indicated that loss of CDKN2 protein function could be related to retinoblastoma (RB) protein overexpression by immunohistochemical analysis, since CDKN2 could induce transcriptional down-regulation of RB, and its loss might lead to aberrant RB regulation. Another tumor-suppressor candidate on the short arm is Bcl2-associated gene 1 (BAG1), located at 9p12.…”
Section: Discussionmentioning
confidence: 99%